Globalizing urban resilience. Issue 8 (14th September 2018) - Leitner, Helga; Sheppard, Eric; Webber, Sophie; Colven, Emma
ABSTRACT: Urban resilience, a new urban development and governance agenda, is being rolled out from the top down by a network of public, private, non-profit sector actors forming a global urban resilience complex: producing norms that circulate globally, creating assessment tools rendering urban resilience technical and managerial, and commodifying urban resilience such that private sector involvement becomes integral to urban development planning and governance. The Rockefeller Foundation's 100 Resilience Cities Program is at the center of this complex, working with the World Bank, global consultants, NGOs, and private sector service providers to enroll cities, develop and circulate urban resilience assessment tools, and create a market catalyzed by the notion of a resilience dividend. Notwithstanding the claim of this program being open and inclusive, aspects of its initial operationalization in Jakarta suggest that urban resilience assessment tools preempt alternative understandings of urban resilience and marginalizing voices of the city's most vulnerable populations.